2015
DOI: 10.14314/polimery.2015.411
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulation studies on filling imbalance in geometrically balanced runner systems of multi-cavity injection molds

Abstract: Przeprowadzono badania dooewiadczalne zjawiska nierównomiernego wype³niania wielogniazdowych form wtryskowych zrównowa¿onych geometrycznie, podczas wtryskiwania tworzyw amorficznych i czêoeciowo krystalicznych, z zastosowaniem ró¿nych rozwi¹zañ konstrukcyjnych kana-³ów doprowadzaj¹cych. Wykonano badania symulacyjne wp³ywu warunków wtryskiwania (natê¿enia przep³ywu i temperatury ch³odzenia) na stopieñ nierównomiernooeci wype³nienia formy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Moreover, a flexible meshing was applied to provide high-resolution mesh for the runners and the cavity. Several simulation studies have confirmed this approach [22][23][24][25].…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, a flexible meshing was applied to provide high-resolution mesh for the runners and the cavity. Several simulation studies have confirmed this approach [22][23][24][25].…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, a flexible meshing comprising different element topologies was applied to provide high‐resolution mesh for the runner system and cavity. Several simulation studies have confirmed this simulation approach . Recently, the radial function method RFM was applied to model the flow and heat transfer in the runner systems.…”
Section: Introductionmentioning
confidence: 91%
“…The problem of filling imbalance has been studied by researchers for years . However, there are not solutions that would be universally accepted by engineers, producers, and researchers.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed the composite models of this inverse computation approach for closely intermeshing counterrotating twin screw extruders, 35,36 as other researchers have done for corotating twin screw extruders. [37][38][39] However, those composite models using one-stage melting models were simpler in execution, and the melting regions were clearly specified in those cases.…”
Section: Computationsmentioning
confidence: 99%